Hyalella luciae (Crustacea, Amphipoda, Hyalellidae)—a new species of freshwater amphipod from Southern Brazil - Limberger, Márcio; Santos, Sandro; Castiglioni, Daniela Da Silva (Zootaxa, 2022)
Currently, the freshwater amphipod Hyalella Smith, 1874 includes 91 valid species distributed only in the Americas. This study describes the fifth species for the Várzea River basin, located in the northwestern region of the state of Rio Grande do Sul, Southern Brazil. Among its most prominent features are the presence of the curve seta on the inner ramus of uropod 1 of the males, sternal gills on segments 2-7, propodus ventral face of the gnathopod 1 with nine serrate setae and several small simple and triangular setae, peduncle of uropod 3 with 11-12 distal cuspidate setae with accessory setae, and telson with fifteen cuspidate setae with accessory setae distributed on distal margin. This study presents a detailed comparison of the species we are describing with those already discovered. The diversity of freshwater amphipods in southern Brazil is intriguing. Further investigations should open the way to elucidate the evolutionary history of these crustaceans, uncovering the potential and patterns of diversification of the genus Hyalella.